Synergic effect of millet husk ash and wheat straw ash on the fresh and hardened properties of Metakaolin-based self-compacting geopolymer concrete - Bheel, N. (Elsevier Ltd, 2021)
This experimental work explored the synergic effect of millet husk ash (MHA) and wheat straw ash (WSA) on the fresh and hardened properties of metakaolin-based self-compacting geopolymer concrete. An equal amount of MHA and WSA contents at 2.5, 5, 7.5 and 10 were utilized as a partial replacement of metakaolin in the mixes. The filling ability (slump flow, V-Funnel, and T50 flow) and passing ability (J-Ring and L-box) of fresh SCGC mixture were determined. The study further determined the density, compressive, split tensile and flexural strength and permeability of hardened SCGC mixes. The results showed that both MHA and WSA addition somewhat reduced in workability of fresh SCGC mixes. However, the hardened properties were significantly enhanced, a development that was more pronounced in the mix having 5 each of MHA and WSA with compressive strength, split tensile strength, and flexural strength of 53.80 MPa, 4.82 MPa, and 5.15 MPa, respectively. The water penetration depth and density of SCGC mixes lessen as the MHA and WSA contents were increased beyond 10. Overall, the study recommends a combined use of 5 each of MHA and WSA for metakaolin-based geopolymer SCC production to ensure optimal performance. Â© 2021 The Authors